Waqf Management: A Bibliometric Review (UIN Sunan Kudus, 2022)
This study aimed to create a map of the evolution of waqf management research in indexed journals. This study analyzed keywords, topics, journals, and authors that were published in the Scopus database. This study focuses on a journal published between 2016 and 2021. This year was chosen because waqf management research has continued to advance since 2016. In addition, the scope of this study is restricted to three disciplines: social finance; economics, econometrics, and finance; and business, management, and accounting. There were a total of 93 articles that matched the year and topic criteria. Utilizing the Vosviewer application, the data is processed to determine the bibliometric mapping associated with the advancement of Waqf Management research. As indicated by the findings, the study's focus on waqf management has continued to evolve over the past six years. According to the results of the bibliometric analysis, the Waqf Management theme generates five clusters. Cluster 1 includes 15 topics. Cluster 2 includes 6 issues. Cluster 3 includes 4 issues. And Cluster 9 includes 2 issues. This study also demonstrates the need for further research on Waqf Management as a result of the proliferation of contemporary waqf products resulting from the development of waqf studies. This is necessary to preserve the integrity of the waqf and the management of waqf assets so that they remain within the sharia corridor. Since there isn't a clear way to tell if the performance of waqf institutions has gone up or down, one of the most important areas of research is the creation of performance criteria for waqf institutions.